Democratic Equality : What Went Wrong? - Broadbent, Ed, 1936- (Book collections on Project MUSE., 2001)
Are the world's oldest democracies failing? For most of the past fifty years democratic governments made determined and successful efforts at overcoming the significant inequalities that are the by-product of a capitalist economy. During this period a new concept of democratic citizenship that added social and economic rights to the liberal legacy of political and civil liberties established roots in most North Atlantic democracies. Since the 1980s this notion of democratic citizenship has been challenged ideologically to such a degree that through either major modification or complete elimination of programs, equality as a fundamental democratic goal is disappearing in many nations -- particularly in the Anglo-American democracies. In this extraordinary collection, top scholars in political science, sociology, philosophy and economics, discuss this radical shift towards inequality in an age of mass capital globalization. Wide ranging in topic yet coherent in approach, Inequality and the Modern Democratic State comprises thirteen essays, including Ed Broadbent's "Ten Propositions about Equality and Democracy", Robert Hackett's "Watch Dogs, Mad Dogs, or Lap Dogs?: News Media and Civic Equality" and Barbara Ehrenreich's "Inequality in the Clinton Era". Many European democracies, argue the contributors, have adapted to new circumstance in the global economy without resorting to policies that actively promote inequality. While differing in some important details on solutions, they all contend that the political decision-making process is of critical importance in entrenching, or battling, an escalating inequality that is neither necessary nor desirable.